Comparison of skull morphology between two chevrotain species of Tragulus genus (Mammalia: Artiodactyla) in Vietnam - Hoang Quoc, Huy; Nguyễn Trường , Sơn; Bùi Anh, Tuấn; Trần Văn, Giang; Ngô Đắc, Chứng (Hue University Journal of Science: Natural Science, 2026)
In Vietnam, two chevrotain species of the genus Tragulus are recorded: the Vietnam chevrotain (T. versicolor) and the Lesser mousedeer (T. kanchil). This study analysed 26 cranial morphological parameters from 27 adult skull specimens (7 T. versicolor and 20 T. kanchil) to identify diagnostic characteristics between the two species. Descriptive statistics, Principal component analysis, Mann-Whitney U test, and MANOVA all revealed clear differences in overall skull morphology. Six skull and jaw length parameters –– basal-palatal length, mandible length, condylobasal length, maxillary lateral length, lower tooth row length, and upper tooth row length –– were the most consistent and distinctive for distinguishing the two species. These findings provide the first set of morphological criteria for identifying and classifying Tragulus species in Vietnam and also support conservation work and specimen identification.